Adsorption of chloroquine and hydroxychloroquine as potential drugs for SARS-CoV-2 infection on BC3 nanosheets: a DFT study. (10th September 2021) - Rahimi, Rezvan; Solimannejad, Mohammad; Farghadani, Mohadeseh
Abstract : The adsorption of HCQ on BC3 nanosheets is stronger than that of CQ. The hydrogenated BC3 nanosheet is a more prominent nanocarrier for the CQ and HCQ drugs than the bare BC3 monolayer. Abstract : The adsorption of chloroquine (CQ) and hydroxychloroquine (HCQ) on BC3 nanosheets was evaluated and compared in gas and water media. The most desired complexes were obtained when the drug is parallel to the BC3 surface, with an adsorption energy of −1.69 and −1.77 eV for CQ/bare and CQ/hydrogenated BC3 complexes, respectively. The corresponding adsorption energies for HCQ/bare and HCQ/hydrogenated BC3 nanosheets are −1.78 and −1.99 eV, respectively. It was found that the BC3 nanosheets could be a suitable carrier of CQ and HCQ drugs, considering the amount of adsorption energy in the gas phase and water environment. The hydrogenated BC3 nanosheet is a more prominent nanocarrier for CQ and HCQ than the bare BC3 monolayer.